Green Synthesis of Silver Nanoparticles: Estimation of their Antimicrobial Activity and their Electrochemical Fabrication on FTOs - Zeshan Ahmad; Syeda Rubina Gilani (Pakistan Journal of Analytical & Environmental Chemistry)
The research project focused on fabricating the conducting Fluorinated Tin Oxide (FTO) glass with green synthesized metallic nanoparticles (NPs) of silver. Stable and size-controlled metallic nanoparticles of silver were synthesized by using lemon leaf extracts. One-pot, clean, and ecofriendly synthesizing strategy led to spherical-shaped metallic nanoparticles having a particle size range between 5–50 nm. Characterization techniques like SEM, XRD, and Particle size analyzer revealed the synthesis of well-formed spherical nanoparticles. In UV-Visible spectra, the plasmonic peaks of silver NPs in regions between 40 0-450 nm also confirmed the formation of NPs. FTO plates were fabricated by depositing fine and uniform layers of nanoparticles, using the electrochemical method. These silver NPs were successfully used for electro-catalytic water splitting and showed a low onset potential ~1.5V at room temperature. Silver NPs showed moderate bactericidal activity against Gram-positive and Gram-negative bacteria.